Molecular control of the floral transition in the mast seeding plant Celmisia lyallii (Asteraceae). Issue 8 (15th March 2021) - Samarth,; Lee, Robyn; Kelly, Dave; Turnbull, Matthew H.; Macknight, Richard C.; Poole, Anthony M.; Jameson, Paula E.
Abstract: Mast flowering (or masting) is synchronous, highly variable flowering among years in populations of perennial plants. Despite having widespread consequences for seed consumers, endangered fauna and human health, masting is hard to predict. While observational studies show links to various weather patterns in different plant species, the mechanism(s) underpinning the regulation of masting is still not fully explained. We studied floral induction in Celmisia lyallii (Asteraceae), a mast flowering herbaceous alpine perennial, comparing gene expression in flowering and nonflowering plants. We performed translocation experiments to induce the floral transition in C. lyallii plants followed by both global and targeted expression analysis of flowering‐pathway genes. Differential expression analysis showed elevated expression of ClSOC1 and ClmiR172 (promoters of flowering) in leaves of plants that subsequently flowered, in contrast to elevated expression of ClAFT and ClTOE1 (repressors of flowering) in leaves of plants that did not flower. The warm summer conditions that promoted flowering led to differential regulation of age and hormonal pathway genes, including ClmiR172 and ClGA20ox2, known to repress the expression of floral repressors and permit flowering. Upregulated expression of epigenetic modifiers of floral promoters also suggests that plants may maintain a novel "summer memory" across years to induce flowering. These results provide a basic mechanistic understanding of floral induction in masting plants and evidence of their ability to imprint various environmental cues to synchronize flowering, allowing us to better predict masting events under climate change.